PENGARUH HARGA, IKLAN, CITRA MERK, DAN PELAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN MOBIL WULING DI WILAYAH SURAKARTA - Suryo, Aryoto Adhi; Suddin, Alwi; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study entitled aims to explain the effect of price, advertising, brand image, and after sales service on purchasing decisions. In sampling, this study uses a purposive sampling technique, Data collection techniques were carried out by distributing questionnaires, sending via WA and interviewing 97 people directly in Wuling car users in the Surakarta Region.Data processing and analysis methods use qualitative analysis which includes the interpretation of data obtained in research as well as the results of data processing that have been carried out by providing information and explanations, as well as quantitative analysis which includes validity and reliability tests, classic assumption tests, multiple regression analysis, hypothesis testing through F test and t test and analysis of the coefficient of determination (R2).